The Concept of Sunnah: Its Evolution and Implications for Modern Islamic Thought - Unggul Prayoga; Tesa Maulana; Munawir (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Sunnah and hadith are two fundamental concepts in Islam that serve as guidelines for the lives of Muslims. This study aims to analyze the development of the meaning of sunnah and hadith from the perspective of classical to contemporary scholars, as well as to explore the transformation of sunnah from the practices of the Prophet Muhammad SAW into canonized hadith texts. The method used is a historical literature review, referring to classical books, as well as the thoughts of scholars such as Imam Shafi'i and Fazlur Rahman, and modern literature. The results of the study show that the Sunnah was initially understood as the practical traditions of the Prophet, while hadiths were verbal narratives about his words, deeds, and decisions. Differences in interpretation arose among scholars, such as muhaddithun who viewed the Sunnah comprehensively, ushuliyyun who emphasized legal aspects, and fuqaha who classified it into categories of fiqh. Fazlur Rahman put forward a theory of the evolution of the Sunnah into hadith through three phases: informal, semi-formal, and formal, in which the dynamic Sunnah changed into a more rigid text. This research makes a significant contribution to understanding the development of the concept of Sunnah and its implications for contemporary Islamic thought.